2019
DOI: 10.1371/journal.pone.0212059
|View full text |Cite
|
Sign up to set email alerts
|

Stable expression of aquaporins and hypoxia-responsive genes in adventitious roots are linked to maintaining hydraulic conductance in tobacco (Nicotiana tabacum) exposed to root hypoxia

Abstract: Formation of adventitious roots in plants is a common response to hypoxia caused by flooding. In tobacco, after one week of root hypoxia treatment, plants produced twice as many adventitious roots as the aerated plants, but their maximum length was reduced. Hypoxia severely reduced net photosynthesis, transpiration rates, and photosynthetic light responses. Relative transcript abundance of the examined aquaporins in lateral roots was reduced by hypoxia, but in adventitious roots it remained unchanged. This app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 69 publications
(91 reference statements)
3
21
0
Order By: Relevance
“…The latter study demonstrated that beside PIP1;3, PIP1;1 was also down-regulated after 2 days of hypoxia treatment. Moreover, down-regulation of other AQP encoding genes such as PIP1;2, PIP1;4, PIP2;1 in LR, was observed after one week of hypoxia treatment 99 . The authors did not observe any difference in hydraulic conductance (K r ) between hypoxic and aerated plants, indicating the efficiency of AR in root water transport in tobacco.…”
Section: Wvd2 Wave-dampened 2; Pp2-a12 Phloem Protein 2-a12 Tub1 mentioning
confidence: 94%
“…The latter study demonstrated that beside PIP1;3, PIP1;1 was also down-regulated after 2 days of hypoxia treatment. Moreover, down-regulation of other AQP encoding genes such as PIP1;2, PIP1;4, PIP2;1 in LR, was observed after one week of hypoxia treatment 99 . The authors did not observe any difference in hydraulic conductance (K r ) between hypoxic and aerated plants, indicating the efficiency of AR in root water transport in tobacco.…”
Section: Wvd2 Wave-dampened 2; Pp2-a12 Phloem Protein 2-a12 Tub1 mentioning
confidence: 94%
“…Water absorption by roots is at least partially ( ~ 50%) governed by root water channels (aquaporins) of the plasma membrane intrinsic protein (PIP) family (McElrone et al, 2007; Tournaire‐Roux et al, 2003). The production of PIPs aquaporin‐like proteins differs between anaerobic and aerobic conditions among several soybean cultivars with varying degrees of waterlogging tolerance (Jitsuyama, 2017; Tan & Zwiazek, 2019). Incorporating this trait into crop models may help to account for genetic diversity for waterlogging tolerance under waterlogging conditions.…”
Section: Plant Physiological Processes That Should Inform Future Modementioning
confidence: 99%
“…Beside constitutive AR, plants can produce AR in response to the environment: in response to anoxia stress provoked by flooding [36,37], to dark-light transitions such as a dark storage period condition for cuttings or light control of auxin homeostasis [38,39,40], to stem cutting [12,21,39,41] and to hormones [17,42]. Table 1 provides a non-exhaustive list of species for which adventitious roots are described in the present review.…”
Section: When Are the Adventitious Roots Produced?mentioning
confidence: 99%
“…In Arabidopsis, inhibition of growth of the main root system and the promotion of AR elongation under hypoxia restrict the root system in upper soil layers where the oxygen shortage may last for shorter time periods [36]. This is also supported by the observation of tobacco plants producing more AR in the hypoxia condition, but with reduced maximum length [37]. AR can contribute to flooding adaptation by taking up oxygen [38,55].…”
Section: When Are the Adventitious Roots Produced?mentioning
confidence: 99%
See 1 more Smart Citation